1991
DOI: 10.1037/h0084301
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of solution strategy to spatial performance.

Abstract: In a series of studies three solution strategies for spatial problems were identified: a mental rotation strategy, a perspective change strategy, and an analytic strategy. The test-retest reliability, validity, and general inability of a measure of these strategics was established. This measure, the Spatial Strategy Questionnaire, was then used to assess the role of solution strategy in the spatial performance of 243 undergraduates. Hierarchical regression analyses revealed that solution strategy accounted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 45 publications
2
81
1
2
Order By: Relevance
“…On the basis of similar instruments employed by Freedman and Rovegno (1981), Schultz (1991), and Peters et al (1995), a multiplechoice questionnaire was used to examine the strategies adopted during the test. In Question 1, the participant used a 1 (never) to 5 (always) scale to indicate how frequently he or she applied each of the seven strategies presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of similar instruments employed by Freedman and Rovegno (1981), Schultz (1991), and Peters et al (1995), a multiplechoice questionnaire was used to examine the strategies adopted during the test. In Question 1, the participant used a 1 (never) to 5 (always) scale to indicate how frequently he or she applied each of the seven strategies presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In standard mental rotation conditions with visual input, two classes of strategies are generally identified: holistic strategies, in which the participants report trying to process the stimuli in a global fashion, and analytic strategies, in which the participants successively consider each stimulus part (Cooper, 1976;Shepard & Cooper, 1982). The participants reporting the holistic strategy of mentally moving the whole three-dimensional stimulus show higher proficiency than do those relying on the analytic strategy of finding key stimulus features and encoding their relative positions (Schultz, 1991). In haptic settings, when feeling simpler two-dimensional forms, many participants report employing similar analytic strategies, relying on verbal labeling (Dodds, 1983) or mentally moving specific features (Dellantonio & Spagnolo, 1990).…”
Section: Mental Rotation Strategiesmentioning
confidence: 99%
“…The present study confirmed that left-right orientation requires two independent mental components: verbal-spatial mapping of left-right to a particular direction of the egocentric frame of reference and egocentric perspective rotation. Similarly, the vast majority of participants are known to adopt a strategy of egocentric perspective rotation (move self) for executing the RMT (Schultz, 1991). This distinction suggests that but neuroimaging studies have not yet narrowed down candidates for the cortical regions involved in perspective transformation (Creem-Regehr, Neil, & Yeh, 2007;Zacks & Michelon, 2005;Zaehle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The low spatial ability individuals also complained that they were unable to visualize the views altogether. 13,16,17,18 . Based on Spatial Strategy Questionnaire, Schultz 18 has identified three solution strategies for spatial problems: a mental rotation strategy, a perspective change strategy, and an analytic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…13,16,17,18 . Based on Spatial Strategy Questionnaire, Schultz 18 has identified three solution strategies for spatial problems: a mental rotation strategy, a perspective change strategy, and an analytic strategy. However, the strategy use in PSVT has not been investigated.…”
Section: Introductionmentioning
confidence: 99%